2013
DOI: 10.1118/1.4793724
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory triggered 4D cone‐beam computed tomography: A novel method to reduce imaging dose

Abstract: Simulation studies have shown that RT 4D CBCT reduces imaging dose while maintaining comparable image quality for phase based 4D CBCT; image quality is degraded for displacement based RT 4D CBCT in its current implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
1
27
0
Order By: Relevance
“…More importantly, we showed that by optimizing the imaging frequency for each individual respiratory phase, projections and thus imaging dose can be evenly spread over all respiratory phases. Cooper et al 15 already showed in a simulation study that this new acquisition technique allows for dose savings of the order of 50%, a result which is broadly in line with our measurements. The remaining small imbalance in the number of projections between the respiratory phases can be explained based on two factors: first, for the 3.5 s breathing period, the time spent in the early-inhale and lateinhale respiratory phases was of the same order as the minimum time between two projections (160 ms).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More importantly, we showed that by optimizing the imaging frequency for each individual respiratory phase, projections and thus imaging dose can be evenly spread over all respiratory phases. Cooper et al 15 already showed in a simulation study that this new acquisition technique allows for dose savings of the order of 50%, a result which is broadly in line with our measurements. The remaining small imbalance in the number of projections between the respiratory phases can be explained based on two factors: first, for the 3.5 s breathing period, the time spent in the early-inhale and lateinhale respiratory phases was of the same order as the minimum time between two projections (160 ms).…”
Section: Discussionsupporting
confidence: 91%
“…Because on-the-fly adaptation of the gantry velocity was not available on our linac platform at the time of the experiments, we were limited to the imaging frequency as optimization parameter. Cooper et al 15 have recently reported on the positive impact of a variable imaging frequency on the total imaging dose in a simulation study.…”
Section: Introductionmentioning
confidence: 99%
“…3.C.2). This also justifies image acquisition techniques such as respiratory triggered-4DCBCT, 26 which reduces additional imaging dose that might otherwise cause projection clustering.…”
Section: D Projection Angular Spacingmentioning
confidence: 90%
“…The standard deviations are non-negligible compared to the average sampling interval, which are caused by the ‘clustering’ and ‘gap’ [29] seen in the phase-binned slow-gantry projections. The step-and-shoot technique [11], which acquires fluoroscopy for over a respiratory cycle at preselected scan angles, is an acquisition technique that can avoid the ‘clustering’ and ‘gap’ to achieve evenly spaced projections.…”
Section: Methodsmentioning
confidence: 99%
“…However, step-and-shoot technique is not used in this study, because the current developer mode of Varian TrueBeam machines does not support very low frame rate acquisition (below 3 fps), which makes the dose of step-and-shoot technique much higher than the slow-gantry technique. Besides the step-and-shoot technique, recently developed active acquisition technique triggered by tracked tumor motion [2931] can also achieve more evenly-spaced projections through adjusting gantry rotation speed/acquisition frame rate or dropping excessive projections. Due to the lack of supporting hardware and software, they were not used in this study either.…”
Section: Methodsmentioning
confidence: 99%